2019
DOI: 10.1590/1983-21252019v32n211rc
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVITY OF BENTAZON AND NICOSULFURON IN Crotalaria spectabilis INTERCROPPED WITH MAIZE CULTURE

Abstract: Corn intercropped with showy crotalaria allows better use of the agricultural year, having in the same period, economic return from grain yield and the benefits of the legume. The objective was to study the selectivity of the herbicides bentazon and nicosulfuron to C. spectabilis, the weed control and the corn development intercropping system. Two experiments were conducted in the field, one in late-season and the other one in regular growing season. The experimental design was the randomized block, with fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In the case of C. ochroleuca, the dose of 3 g/ha of metsulfuron-methyl promoted a mortality of 80% (Figure 5). The Nicossulfuron, classified in the chemical group of ALS inhibitors (Acetolactate Synthase Enzyme), just like the Methyl Metsulfuron analyzed in this study, was selective for C. spectabilis in a post-emergence application study using the herbicides nicossulfuron and bentazon (24) . Thus, the dose of 0.75 g/ha, below that recommended by the manufacturer, is the most advisable for application in the desiccation of C. ochroleuca, aiming at the establishment of the species.…”
Section: Resultsmentioning
confidence: 83%
“…In the case of C. ochroleuca, the dose of 3 g/ha of metsulfuron-methyl promoted a mortality of 80% (Figure 5). The Nicossulfuron, classified in the chemical group of ALS inhibitors (Acetolactate Synthase Enzyme), just like the Methyl Metsulfuron analyzed in this study, was selective for C. spectabilis in a post-emergence application study using the herbicides nicossulfuron and bentazon (24) . Thus, the dose of 0.75 g/ha, below that recommended by the manufacturer, is the most advisable for application in the desiccation of C. ochroleuca, aiming at the establishment of the species.…”
Section: Resultsmentioning
confidence: 83%
“…The authors also report that due to these characteristics, atrazine and mesotrione should not be placed in the crotalaria culture because they were not selective. Nogueira et al (2019) concluded that a dose of 48 g ha -1 of nicosulfuron resulted in high weed control in C. spectabilis; however, this dose resulted in a phytotoxic effect of 81.3% at 42 DAA, significantly reducing its biomass. In this sense, the authors emphasize that C. spectabilis is a plant with C3 photosynthetic metabolism, with slow initial growth and that the application of nicosulfuron slows down this vegetative development even more, a fact that can significantly reduce the biomass of this crop in competition with maize and/or weeds.…”
Section: Discussionmentioning
confidence: 99%
“…Crotalaria spectabilis is a species of the legume family, originally from the Indo-Malay region, with an annual cycle and distributed around the world [1]. It is a plant widely used in the agricultural production system, whether in the succession of crops or intercropped with other crops [2].…”
Section: Introductionmentioning
confidence: 99%